PENGUKURAN OVERALL EQUIPMENT EFFECTIVENESS PADA PROSES PEMOTONGAN INDUSTRI FURNITURE - Yohanes Anton Nugroho (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2023)
The sawmill machine is one of the machines highly used in the cutting process n furniture production at PT X. The sawmill machine used at PT X experiences various problems, including damage and damage repair time in more than 15% of the total production time. The event of machine failures also causes several impacts, such as low target achievement and non-uniform quality. The Overall Equipment Effectiveness (OEE) gets an average OEE value for the period January 2021 - June 2021 of 46.79%, which is still far from the ideal standard value of Overall Equipment Effectiveness, which is 85%. Factors that greatly influence the low value of OEE based on. The sixth significant losses analysis is rework losses of 17.48%, followed by breakdown losses and reduced speed losses, which both have a percentage of 16.12%. Meanwhile, for Set up and Adjustment Loss, Idling Minor Stoppage, and Scrap or Yield Loss, the portions are relatively small, less than 5%.